Development of PVDF Membrane with PEG Coating for CO2 and CH4 Gas Separation - Noor Farahin, Sazali (2012)
Thin film composite membranes were prepared for separation of carbon dioxide from methane using polyvinylidene fluoride (PVDF) as support and polyethylene glycol (PEG) as active layer at various concentrations. Permeance and the ideal selectivity were measured for all membranes under the feed pressure 1 and 2 bar. Influences of affecting parameters on membrane performance (permeances and selectivity) were investigated. For all coated membranes, the carbon dioxide permeance was higher compared to the methane permeances. The SEM study was carried out for investigation of membrane pore sizes. The membranes are coated with 2%, 4% and 6% PEG. For surface image of the membranes were identified by using scanning electron microscopy (SEM). The SEM images exhibited the best surface image with large pores was discovered at concentration 2% PEG. Membranes were also characterized using Fourier Transform Infrared Spectroscopy (FTIR) to detect the presence of PEG functional group in the membrane. The performance of the membrane was proven by conducting the gas permeation test. The selectivity of CO2/CH4 at 1 bar was 1.117 (2% PEG) and at 2 bar was 1.155 (6% PEG). Hence, coated membranes were discovered to affect the pore sizes which will consequently affect the permeability and selectivity of PVDF thin film composite membrane. As a conclusion, the increasing value of PEG coating concentration, the greater the feed pressure should be applied due to the resistance of membrane.